Btp Proteins from Brucella abortus Modulate the Lung Innate Immune Response to Infection by the Respiratory Route - Hielpos, Maria Soledad; Ferrero, Mariana C.; Fernández, Andrea G.; Falivene, Juliana; Vanzulli, Silvia; Comerci, Diego J.; Baldi, Pablo C. (Frontiers in Immunology, 2017)
Although inhalation of infected aerosols is a frequent route for Brucella infection in humans, it rarely causes pulmonary clinical manifestations, suggesting a mild or nearly absent local inflammatory response. The goal of this study was to characterize the early innate immune response to intratracheal infection with Brucella abortus in mice and to evaluate whether itis modulated by this pathogen. After infection with 106 CFU of B. abortus, the pulmonary bacterial burden at 7 days p.i. was comparable to the initial inoculum, despitean initial transient decline. Brucella was detected in spleen and liver as early as one day p.i.IL-1β and MCP-1 increased at 3 days p.i., whereas IL-12, KC, TNF-α and IFN-γ only increased at 7 days p.i. Histological examination did not reveal peribronchial or perivascular infiltrates in infected mice. Experiments were conducted to evaluate if the limited inflammatory lung response to B. abortusis caused bya bacterial mechanism of TLR signaling inhibition. Whereas inoculation of E. coli LPS to control mice (PBS/LPS) caused lung inflammation, almost no histological changes were observed in mice preinfected intratracheally with B. abortus (WT/LPS). We speculated that the Brucella TIR-containing proteins (Btps) A and B, which impair TLR signaling in vitro, may be involved in this modulation. After LPS challenge, mice preinfected with the B. abortus btpAbtpB double mutant exhibited a stronger pulmonary polymorphonuclear infiltrate than WT/LPS mice, although milder than that of the PBS/LPS group. In addition, lungs from B. abortus btpAbtpB infected mice presented a stronger inflammatory infiltrate than those infected with the WT strain, and at day 7 p.i. the pulmonary levels of KC, MCP-1 and IL-12 were higher in mice infected with the mutant. This study shows that B. abortus infection produces a mild proinflammatory response in murine lungs, partially due to immune modulation by its Btp proteins. This may facilitate its survival and dissemination to peripheral organs.